Profitability's Critical Role in Shaping Capital Structure Dynamic: Peran Penting Profitabilitas dalam Membentuk Dinamika Struktur Modal - Rizky Nur Wahyuningsih; Eny Maryanti (Academia Open, 2024)
This study examines the impact of asset structure, liquidity, and sales growth on capital structure, with profitability as a moderating variable. Using data from Consumption Sector Manufacturing Companies listed on the IDX between 2018 and 2020, the research employs Partial Least Square (PLS) analysis on a sample of 16 qualified companies selected through Purposive Sampling. Results indicate that asset structure significantly influences capital structure, while liquidity and sales growth have no direct effect. Profitability moderates the relationship between liquidity and capital structure but does not moderate the impact of sales growth. This research contributes to understanding capital structure decisions in the Indonesian manufacturing sector, offering insights for financial managers and policymakers. Highlights: Asset structure drives capital decisions, leveraging debt for expansion. Profitability moderates liquidity's impact on capital structure. Insights aid financial managers in understanding manufacturing sector dynamics. Keywords: Capital structure, Asset structure, Liquidity, Profitability, Manufacturing sector